Preservation of In Vitro Grown Shoot Tips of Potato (Solanum tuberosum L.) by Different Methods of Cryopreservation - Dhital, Shambhu P.; Manandhar, Hira K.; Lim, Hak T. (Nepal Journal of Science and Technology, 2010)
Cryopreservation has been recognized as a practical and efficient tool for long-term storage of vegetatively propagated plants. This study was conducted to investigate the effects of sucrose concentration, hardening temperature and different cryopreservation methods on the survival rate of potato shoot tips after cryopreservation. Excised shoot tips of in vitro plantlets of potato cultivars, Atlantic and Superior were cryopreserved by vitrification, encapsulationvitrification and encapsulation-dehydration. Cryopreservation by vitrification method was used to determine the optimum concentration of sucrose and cold hardening temperature during sub-culturing period to the donor plantlets. Nine-percent sucrose gave 46.7% survival in Atlantic and 40% in Superior. The most optimum hardening temperature for 50% survival in Atlantic and 43.3% in Superior was 10°C. In the case of comparative study of three different cryopreservation methods, the highest survival (52%) as well as regeneration (46%) were observed when the shoot tips were cryopreserved by encapsulation-vitrification method, and the lowest survival (36%) and regeneration (28%) from the vitrification. Plant and tuber morphology of potato regenerated after cryopreservation were similar to those of the non-cryopreserved in vitro plantlets (control). Thus, this study demonstrated that encapsulation-vitrification method was the most effective one among other methods for higher survival as well as regeneration in in vitro shoot tips of potato. Key words: Cryopreservation; Dehydration; Encapsulation; Potato; Regeneration; Vitrification DOI: 10.3126/njst.v10i0.2804 Nepal Journal of Science and Technology Volume 10, 2009 December Page: 15-20